EGFR-targeted affibody–polyIC polyplex kills EGFR-overexpressing cancer cells without activating the EGFR - Anne Pettikiriarachchi; Yelena Ugolev; Richard Birkinshaw; Ahmad Wardak; Maree C. Faux; Timothy E. Adams; Salim Joubran; Alexei Shir; Nufar Edinger; Maya Zigler; Alexander Levitzki; Antony W. Burgess (PLoS ONE, 2026)
The epidermal growth factor receptor (EGFR) is aberrantly activated in many human epithelial cancers. This report presents the preparation, purification, and the anti-cancer potency of an anti-EGFR affibody (Z EGFR 1907’ )-polyethylenimine (PEI)-polyIC complex (PPEA-polyplex). Surface plasmon resonance analysis showed that the Z EGFR 1907’ affibody binds tightly to full-length sEGFR with an average equilibrium dissociation constant, K D, value of 6.74 nM. As expected the PPEA-polyplex does not activate the EGFR kinase, but kills tumor cells expressing medium to high levels of EGFR. The PPEA-polyplex stimulates the release of chemotactic cytokines (e.g., GRO-α, IFN-γ–inducible protein-10) and promoted PBMC-mediated bystander killing of non-treated tumor cells. The PPEA-polyplex also inhibited the growth of human epidermoid vulval carcinoma (A431) xenografts growing in immunocompromised nude mice. Both the in vitro and in vivo results indicate that PPEA-polyplexes have the potential to inhibit the growth of tumors which over-express the EGFR, including colon and breast cancer cells.